Pasang Surut Kuasa Bangsawan dalam Proses Demokratisasi di Bone - Ernawati Ernawati (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This paper will analyze the power of the nobles who had differences in the results of the executive and legislature in Bone regency. The argument that the authors have built is the persistence of aristocratic power in the executive, but declined in the legislature due to several things, one of which, the declining power of Golkar in the legislature. Although, basically remained in power Golkar executive evident during the Election Day since 2003 in the district Bone current period (2013-2018) the candidate regent and deputy regent who win elections have never stretcher parties other than Golkar. Golkar Party, the nobility, and Bone did have a close bond complex to be separated. Bone is a barn Golkar in South Sulawesi.